Antimicrobial pectin-gellan films: effects on three foodborne pathogens in a meat medium, and selected physical-mechanical properties. Issue 1 (1st January 2018) - Trejo-González, Lorena; Rodríguez-Hernández, Adriana-Inés; del Rocío López-Cuellar, Ma.; Martínez-Juárez, Víctor-Manuel; Chavarría-Hernández, Norberto
ABSTRACT: It is first reported the elaboration and characterization of films (F2) containing 1% (w/v) citrus pectin, 0.2% (w/v) gellan gum, 0.5% (w/v) glycerol, CaCl2 5 mM, ethylenediaminetetraacetic acid (EDTA) 0.05 M and 90 (Arbitrary Units)/mL of an antimicrobial concentrated supernatant (ACS) from fermentation culture broths of the lactic acid bacterium, Streptococcus infantarius . The functional films inhibited the growth of Listeria monocytogenes, Escherichia coli and Staphylococcus aureus in "Barbacoa" medium in 7-day cultures at 35°C. " Barbacoa" is a highly appreciated Mexican meat product. In contrast, the control cultures exhibited bacterial-growths up to 10 7 –10 9 (Colony-Forming Units)/g. An antimicrobial-activity synergy between ACS and EDTA was demonstrated. Some film-physical properties were modified by the EDTA-ACS incorporation [F2/control-film]: Young's modulus (MPa), 1, 394/707; elongation at break (%), 1.9/9.3; stress at break (MPa), 5.7/12.6; water vapor permeability (10 –11  g m Pa −1  s −1  m −2 ), 3/20 and oxygen permeability (10 –12  g m Pa −1  s −1  m −2 ), 1.9/1.2.